Ideokinesis : a creative approach to human movement and body alignment - Bernard, Ane (North Atlantic Books, 2014)
Mabel Elsworth Todd pioneered ideokinesis in the 1920s. Her book, The Thinking Body, described new ways to use all the senses as well as inner feeling and imagination to retrain the body to move with ease and balance. The system became an invaluable tool for generations of dancers, actors, and performance artists, thanks largely to one of its most important teachers, AndrE Bernard (1924-2003). This book presents an introduction to the practice as well as a lengthy interview with Bernard and two meticulously detailed workshop protocols illustrated with 52 photographs and line drawings.